Feasibility of using pedometers in a state-based surveillance system: 2014 Arizona Behavioral Risk Factor Surveillance System - Alberto Flórez-Pregonero; Janet E. Fulton; Joan M. Dorn; Barbara E. Ainsworth (Elsevier, 2018)
Background: Despite their utility in accessing ambulatory movement, pedometers have not been used consistently to monitor physical activity in U.S. surveillance systems. This study was designed to determine the feasibility of using pedometers to assess daily steps taken in a sub-sample of adults from Maricopa County who completed the 2014 Arizona Behavioral Risk Factor Surveillance System Survey. Methods: Respondents were sent an Omron HJ324U pedometer, a logbook to record steps taken, and a walking questionnaire. The pedometer was worn for 7 days. Feasibility was assessed for acceptability (interest in study), demand (procedures followed correctly), implementation (time to complete study), and practicality (cost). Results: Acceptability was modest with 23.9% (830/3476) agreeing to participate. Among those participating (92.9%; 771/830), 50.1% (386/771) returned the logbook. Demand was modest with 39.3% (303/771) of logbooks returned with valid data. Implementation represented 5 months to recruit participants. The cost to obtain valid step-count data was USD61.60 per person. An average of 6363 ± 3049 steps/day were taken with most participants classified as sedentary (36.0%) or low active (35.6%). Conclusion: The feasibility of using pedometers in a state-based surveillance system is modest at best. Feasibility may potentially be improved with easy-to-use pedometers where data can be electronically downloaded.